Application of contrast-enhanced ultrasonography for gallbladder squamous cell carcinoma: a case report - Ruan, Liqin; Wu, Xiaoyong; Peng, Guiping; Zhang, Jing; Chen, Weili (Frontiers in Oncology, 2024)
Preoperative diagnosis of Gallbladder squamous cell carcinoma (GBSCC) is difficult, and the contrast-enhanced ultrasound (CEUS) pattern has never been reported before. We present a case of GBSCC where CEUS revealed special findings that facilitated early diagnosis. CEUS demonstrated irregular peripheral ring-like enhancement during the arterial phase, with hypoenhancement in the late phases, and an irregular non-enhancing area persistently present in the center of the lesion.